2021
DOI: 10.1080/2162402x.2021.1879530
|View full text |Cite
|
Sign up to set email alerts
|

Stromal-like Wilms tumor cells induce human Natural Killer cell degranulation and display immunomodulatory properties towards NK cells

Abstract: The similarity of stromal-like Wilms tumor (str-WT) cells with mesenchymal stem cells (MSC), suggests their relevant role in the interplay with immune cells in the tumor microenvironment. We investigated the interaction between str-WT cells and NK cells. We observed that str-WT cells expressed some major ligands for activating and inhibitory NK cell receptors. Moreover, they expressed inhibitory checkpoint molecules involved in the negative regulation of anti-tumor immune response. The analysis of the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Recently, it has been suggested that NK cells could play a role in epithelial-to-mesenchymal transition of melanoma cells, favoring their progression to more malignant stages [ 78 ]. Cantoni et al showed that NK cells could efficiently degranulate upon incubation with stromal-like Wilm’s tumor cells whereas, on the other hand, these cells could inhibit NK cells via IDO and PGE2 production [ 79 ]. Finally, TME-associated hypoxia may contribute to partial abrogation of NK cell activity [ 80 , 81 ].…”
Section: Natural Killer Cell Biologymentioning
confidence: 99%
“…Recently, it has been suggested that NK cells could play a role in epithelial-to-mesenchymal transition of melanoma cells, favoring their progression to more malignant stages [ 78 ]. Cantoni et al showed that NK cells could efficiently degranulate upon incubation with stromal-like Wilm’s tumor cells whereas, on the other hand, these cells could inhibit NK cells via IDO and PGE2 production [ 79 ]. Finally, TME-associated hypoxia may contribute to partial abrogation of NK cell activity [ 80 , 81 ].…”
Section: Natural Killer Cell Biologymentioning
confidence: 99%
“…Up to now, the establishment of primary WT cultures expressing a stable phenotype has been difficult, and few cell lines expressing epithelial characteristics, but not blastemal or mesenchymal morphology, have been obtained [ 74 , 76 , 77 , 78 , 79 ]. Until recently, very few studies from different groups have reported the in vitro stabilization of WT primary cultures displaying mesenchymal [ 80 , 81 ], blastemal, or epithelial features [ 82 , 83 , 84 , 85 ]. Royer Pokora et al stabilized in vitro primary cultures from the stromal component (str-WT), and showed that they bear the same mutations as the primary tumors.…”
Section: From Neuroblastoma To Wilms’ Tumor: the Impact On Nk Cellsmentioning
confidence: 99%
“…str-WT exhibited potent inhibitory effects in vitro on the IL-2-induced proliferation of NK cells and on the expression of the activating receptors NKp30, NKp44, NKG2D, and 2B4. All these inhibitory effects were mediated by tumor-derived indoleamine-2,3-dioxygenase (IDO) metabolites and PGE2 [ 80 ].…”
Section: From Neuroblastoma To Wilms’ Tumor: the Impact On Nk Cellsmentioning
confidence: 99%
“…Moreover, MSCs cannot only effectively inhibit IL-2-induced NK cell proliferation but also prevent cytotoxic activity and cytokine production. Notably, indoleamine 2,3-dioxygenase (IDO) and prostaglandin E2 (PGE2) were reported to be the key mediators in MSC-induced inhibition of NK cells [ 73 , 74 ].…”
Section: The Biological Characteristics and Research Status Of Mscsmentioning
confidence: 99%